Analisis Perbandingan Kecepatan Download pada GSM - Sugeng Riyadi; Harjono Harjono (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2013)
In using a product, sometimes people do not really care whether the product is used according to the promotional advertising products, one of which is advertising internet connection service. Internet provider offers many advantages, among which are the product of good data download speeds. This study describes the comparison of the quality of downloaded data using three types of GSM card that is currently widely used by people. Steps being taken in comparing data download speed that is by downloading the data together at the same place and with the same file size. The data taken in this study is the long download process from start to finish downloading. Then performed several tests to determine the speed of the download as well as to determine which card is the fastest to download the data, among other test normality test, homogeneity and different test that includes One Way ANOVA test and Kruskal Wallis test. After testing the parametric and nonparametric known that the card has good speed is of the GSM provider trhree card